Synthesis, antimicrobial properties and in silico studies of aryloxyacetic acid derivatives with hydrazone or thiazolidine-4-one scaffold - ŞENKARDEŞ, SEVİL (My University, 2022)
In this work, twenty hydrazide-hydrazone and 4-thiazolidinone derivatives were synthesized starting from m-cresol. Antimicrobial evaluation was carried out by microdilution method against Enterococcus faecalis and Staphylococcus aureus as Gram-positive bacteria and Escherichia coli and Pseudomonas aeruginosa as Gram-negative bacteria, and three pathogenic fungi Candida albicans, Candida parapsilosis and Candida krusei. Some compounds possessed considerable antimicrobial properties against the tested microorganisms, particularly against E. coli. 4-Thiazolidinones containing 3-methoxyphenyl and 3,5-dichlorophenyl moieties (4h and 4i) were found to be the most active derivatives with MICs of 2 mu g/mL against E. coli. N\"-[(3,5-dichlorophenyl)methylidene]-2-(3-methylphenoxy)acetohydrazide (3i) also displayed antifungal activity against Candida krusei that was comparable to fluconazole. Calculated drug-likeness and ADMET parameters of the most active compounds confirmed their potential as antimicrobial drug candidates. Molecular docking investigations were carried out in the thiamine diphosphate-binding site of pyruvate dehydrogenase multienzyme complex E1 component (PDHc-E1) to clarify the potential antibacterial mechanism against E. coli. The results showed the potential and importance of developing new hydrazones and 4-thiazolidinones that would be effective against microbial strains. Communicated by Ramaswamy H. Sarma
Keywords: Tıp; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyofizik; Biyokimya; Temel Bilimler; Medicine; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Biophysics; Biochemistry; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Yaşam Bilimleri (LIFE); BİYOFİZİK; Biyoloji ve Biyokimya; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); BIOPHYSICS; BIOLOGY & BIOCHEMISTRY; İlaç Keşfi; Biyokimya (tıbbi); Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Drug Discovery; Biochemistry (medical); Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology